Respostas
respondido por:
2
Basta aplicar a prova real: 126 + 97 = 223,
logo Minuendo 223 - Subtraendo 126 = Diferença 97.
Espero ter ajudado e bons estudos!
logo Minuendo 223 - Subtraendo 126 = Diferença 97.
Espero ter ajudado e bons estudos!
respondido por:
1
s = subtraendo
m = minuendo
r = resto
s = m - r
126 = m - 97
126 + 97 = m
223 = m
R: 223
m = minuendo
r = resto
s = m - r
126 = m - 97
126 + 97 = m
223 = m
R: 223
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás